Perspectives of pharmacoecomics development in Ukraine - Yakovleva, O. S.; Яковлева, Ольга Станіславівна (Запорізький державний медичний університет, 2015)
One of the ways of decision of the difficult economic situation in the National Health system and pharmacy is implementation of the Health Technology Assessment (HTA). The application of HTA results obtained on the basis of pharmacoeconomic evaluations, particularly important for the development and permanent improvement of the mechanisms for financing hospitals, the development of means against certain diseases and in the planning of their budget.
Keywords: тези